2019
DOI: 10.1016/j.eururo.2018.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency-induced Thermo-chemotherapy Effect Versus a Second Course of Bacillus Calmette-Guérin or Institutional Standard in Patients with Recurrence of Non–muscle-invasive Bladder Cancer Following Induction or Maintenance Bacillus Calmette-Guérin Therapy (HYMN): A Phase III, Open-label, Randomised Controlled Trial

Abstract: Background There is no effective intravesical second-line therapy for non-muscle invasive bladder cancer (NMIBC) when bacillus Calmette-Guérin (BCG) fails. Objective To compare disease-free survival time (DFS) between radiofrequency-induced thermo-chemotherapy effect (RITE) and institutional standard second-line therapy (control) in NMIBC patients with recurrence following induction/ maintenance BCG. Design, settings, and participants Open-label, phase III randomised controlled trial accrued across 14 centres … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(59 citation statements)
references
References 26 publications
0
46
0
1
Order By: Relevance
“…The authors reported that maintenance BCG was superior to maintenance MMC; however, non‐maintenance BCG had significantly poor efficacy of prophylaxis based on recurrence than MMC 32 . Notably, we did not include chemohyperthermia of MMC because it is still under investigation 33,34 …”
Section: Discussionmentioning
confidence: 99%
“…The authors reported that maintenance BCG was superior to maintenance MMC; however, non‐maintenance BCG had significantly poor efficacy of prophylaxis based on recurrence than MMC 32 . Notably, we did not include chemohyperthermia of MMC because it is still under investigation 33,34 …”
Section: Discussionmentioning
confidence: 99%
“…Patients unresponsive to BCG represent a particular population with a high recurrence risk, for whom radical cystectomy remains the standard and most effective treatment [34][35][36][37]. Several treatment options for the management of these patients are under investigation, and preliminary results of studies using EMDA [38] and CHT [17,39,40] to prevent radical cystectomy have provided promising results. However, one of these studies also highlighted the lack of efficacy of chemotherapy for carcinoma in situ (CIS) [39].…”
Section: Discussionmentioning
confidence: 99%
“…The 10-year disease-free survival rate was increased from 15% in the Mitomycin C arm to 53% in the Mitomycin C plus hyperthermia arm [72]. Two randomized trials demonstrated that Mitomycin C þ Synergo based hyperthermia provides similar or possibly better results compared to standard Bacillus Calmette-Gu erin (BCG) treatment for NMIBC patients [73,74]. Disadvantages of this intracavitary heating approach are an uneven SAR distribution over the bladder wall, and that treatment of more deeply penetrating muscle invasive bladder cancer will require the use of a locoregional hyperthermia device [299,302].…”
Section: Clinical Applications Of Intraluminal Hyperthermia and Hivecmentioning
confidence: 99%
“…Overview of clinical applications of local, locoregional and whole-body heating techniques [55,[71][72][73][74]81,96,97,132,139,166,[199][200][201][202]. BO: Bone (metastases, osteoid osteoma)…”
mentioning
confidence: 99%